2015
DOI: 10.1002/job.2036
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the impact of workforce age diversity on labor productivity: The moderating role of firm size and job security

Abstract: Previous literature has suggested both positive and negative effects of age diversity on labor productivity: positive because of the potential knowledge complementarities between employees of different ages and negative because of the age-related value differences that might reduce cohesion and cooperation, hampering firm performance. Using a Belgian sample of 5892 organizational observations (2008-2011), we unraveled these countervailing effects in two ways. First, we built on prior studies to suggest that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 84 publications
(213 reference statements)
5
80
1
Order By: Relevance
“…We show that identity-based factors like gender and age do not lead to the formation of subgroups. This is opposed to previous findings in other domains [56,57]. We do not find support that identity-based factors like gender and age lead to the formation of subgroups.…”
Section: Theoretical and Practical Contributioncontrasting
confidence: 99%
“…We show that identity-based factors like gender and age do not lead to the formation of subgroups. This is opposed to previous findings in other domains [56,57]. We do not find support that identity-based factors like gender and age lead to the formation of subgroups.…”
Section: Theoretical and Practical Contributioncontrasting
confidence: 99%
“…Additionally, insights from large‐scale, multi‐organizational use of the WICS could add to a growing body of research on conflicting impacts of age diversity on workplace productivity (see Boehm & Kunze, ). De Meulenaere, Boone, and Buyl () showed that age variety's positive impact on productivity was strengthened in larger firms and those with higher job security, and called for more research on moderators of age diversity, including ones that could be affected by human resources policy. Kunze, Boehm, and Bruch () found top managers' lack of negative age stereotypes and the presence of diversity‐friendly human resources policies were organizational‐level moderators of the impact of negative age‐discrimination climate on organizational performance.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge transfer in age-diverse coworker dyads refers to the process whereby two employees who belong to different age groups exchange knowledge with each other, for example, via discussion, imitation, and cooperation (Gerpott, Lehmann-Willenbrock, & Voelpel, 2017). The topic has recently gained importance because demographic changes have altered the age composition of workforces (Shultz & Adams, 2007): First, age diversity is increasing, which means that, in some companies, members of up to four different generations are working side-by-side, thus providing numerous opportunities for interactions between age-diverse coworkers (King & Bryant, 2017;De Meulenaere, Boone, & Buyl, 2016). Second, the number of older workers is increasing, requiring organisations to find ways to retain the valuable knowledge of older workers before they enter retirement (Burmeister & Deller, 2016).…”
Section: Introductionmentioning
confidence: 99%